2005
DOI: 10.1097/00000542-200504000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Does the Amygdala Mediate Anesthetic-induced Amnesia?

Abstract: BLA lesions block sevoflurane-induced amnesia. A role for the BLA in mediating anesthetic-induced amnesia may be a general principle of anesthetic action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(8 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Recent studies also showed that exposure to sevoflurane increased β-amyloid protein levels, which could induce further apoptosis and contribute to or cause POCD [1] , [3] , [43] , [44] , [45] . Sevoflurane at doses from 0.5% to 2.6% administered either during or immediately after a learning task has been shown to inhibit memory retention [46] , [47] , [48] , [49] , [50] . Although the inhalation anesthesia–POCD model has been well documented, it is debated.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies also showed that exposure to sevoflurane increased β-amyloid protein levels, which could induce further apoptosis and contribute to or cause POCD [1] , [3] , [43] , [44] , [45] . Sevoflurane at doses from 0.5% to 2.6% administered either during or immediately after a learning task has been shown to inhibit memory retention [46] , [47] , [48] , [49] , [50] . Although the inhalation anesthesia–POCD model has been well documented, it is debated.…”
Section: Discussionmentioning
confidence: 99%
“…[ 24 ] Also, the sub-anaesthetic doses of sevoflurane have shown memory loss by its action on amygdala through GABA A receptor. [ 25 ] Thus the relationship between the olfactory identification impairment and reduced blood melatonin concentration could be due to the presence of a notable concentration of melatonin-binding sites in entorhinal cortex and the CA1 in the hippocampus which are sites important in pairing odours with the appropriate memory. [ 26 ] The short-term olfactory identification impairment demonstrated with sevoflurane-based anaesthesia suggests a possibility of neurotoxicity which cannot be ruled out in long-term exposure to the patients.…”
Section: Discussionmentioning
confidence: 99%
“…The work of Alkire and Nathan [16] demonstrates that sevoflurane acts on the amygdala and more precisely on its basolateral nucleus, inducing a loss of memory of rats. The amygdala is involved in the emotional processes and other automatic functions [17] like those of memorization [18].…”
Section: Discussionmentioning
confidence: 99%